POSSIBILITIES OF USING INERTIAL MEASUREMENT UNIT SENSOR FOR ASSESSING BALANCE ABILITIES IN THE ELDERLY - Nedovic, Nenad; Mutavdzin Krneta, Slavica; Vujicic, Danilo; Vukov, Dragana; Jovanovic, Stevan; Skvortsov, Dmitry (Srpski medicinski časopis Lekarske komore, 2025)
Aim: This study aimed to evaluate age-related changes in postural stability among healthy older adults using inertial measurement unit (IMU) sensors and assess the clinical potential of wearable technology for balance assessment in geriatric populations. Methods: Thirty-four healthy participants aged > 65 years were divided into two age groups (65–75 and > 75 years). Balance was assessed using a sacrum-mounted IMU sensor during a 30-second semi-tandem stance in three trials. Results: Participants > 75 years showed increased postural sway compared to younger counterparts. Gender differences revealed greater medio-lateral sway in males (p = 0.038). No significant differences were observed in sway velocity or ellipse area, suggesting effective compensatory mechanisms in static conditions. Conclusion: IMU-based balance assessment demonstrates sensitivity in detecting subtle age-related postural changes, with practical advantages for both clinical and community settings.